Answer:
![(11)/(2) ,-(13)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/vgc41e29brwnhcxaya5drskxscbbn024u4.png)
Explanation:
we know That l
l = x when x > 0 and l x l = - x when x <0
for the given equation - 5|3 + 4k| = - 115
when 3 + 4k > 0 the equation becomes
-5(3+4k) = - 115
→ -5 · 3 - 5 · 4k = - 115
→- 20k = - 115 + 15 = - 110
→ k = -
=
![(11)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/aa7afvp17aw2awj9jj0l1238j12og3fkoh.png)
Again when 3 + 4k <0 the equation becomes
-5(-(3+ 4k )) = - 115
→15 + 20k = - 115
→ 20k = - 115 - 15
→ 20k = - 130
⇒ k = -
= -
![(13)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ebresvjqmyi2yd5os0l74x2pe03yi60zcg.png)